Human Rights Protection in Criminal Proceedings under Criminal Procedure Code 2015 - Tran, Thu Hanh (VNU Journal of Science: Legal Studies; Vol 34 No 3, 2018)
Based on the 2013 Constitution, Criminal Procedure Code 2015 pays special attention to the respect and protection of human rights in trial proceedings. Being the core activity of criminal procedure, trial profoundly demonstrates Vienam’s policies of human rights protection. This article uses a rights-based approach to analyze the aspect of human rights protection through Criminal Procedure Code 2015 provisions on the trial phase. These are the regulations on objectives, principles of the Criminal Procedure Code; regulations on trial procedures and other relevant regulations. Keywords: Criminal procedure, judge, human rights, Criminal Procedure Code 2015.